2017
DOI: 10.1002/slct.201700085
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study of the Structures and Photoelectric Properties of Benzodithiophene‐Based Molecules by Replacing Sulfur with a Variety of Heteroatoms (O, N, P, Si, Se)

Abstract: The sulfur atoms on TIB were replaced by oxygen, nitrogen, phosphorus, silicon and selenium atoms to design a serial of new molecules. The bond lengths, dihedral angles, energy levels and energy gaps, ionization potentials, electron affinities, frontier molecular orbitals, absorption and fluorescence spectrums, reorganization energies and charge transfer rates of all molecules were calculated with density functional theory and the time‐dependent density functional theory methods. The results indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This approach offers a better matchup of the solar spectrum and thus attains the high efficiency in photovoltaic cells (PVC) [12]. Recently, many researchers [13,14] have demonstrated that the incorporation of heteroatoms and the side chain into the π-conjugated electron-deficient five-membered ring causes push-pull effect that alters their electronic properties [7].…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers a better matchup of the solar spectrum and thus attains the high efficiency in photovoltaic cells (PVC) [12]. Recently, many researchers [13,14] have demonstrated that the incorporation of heteroatoms and the side chain into the π-conjugated electron-deficient five-membered ring causes push-pull effect that alters their electronic properties [7].…”
Section: Introductionmentioning
confidence: 99%